A STUDY ON THE EFFECT OF YOGA THERAPY ON ANAEMIA IN WOMEN - Sharma, K. Krishna; Prasada H, Thirumaleshwara; K, Udayakumara; B, Savitha (European Scientific Journal, ESJ, 2014)
The main aim of the current study is to finding the effect of yoga therapy on anemia. For this purpose, 23 female Anemic individuals aged between 20-25 years who were willing to participate in the program were selected randomly as subjects from University Hostel for Women and Working Women Hostel, in Mangalore University Campus, Mangalagangothri for 30 days programme from 10th February to 25th March. They were randomly divided into an experimental group and a control group. Yogic practices were progressively introduced to the experimental group on six days in a week for nearly 60 to 70 minutes. The therapy was carried out in the morning from 6.15 am to 7.30 am in Yogic Science Department, Mangalagangothri, Mangalore. The control group was not exposed to any yogic practices. Assessment has been done before and after the study for the parameters Hb%, PCV (Hct), WBC, and PEFR for both the groups. The results of various tests were analyzed using student‘t’ test. After the yoga therapy every variable under Haemogram showed significant improvement among experimental group when compared to control group. Hemoglobin showed a significant improvement with p=0.00002462,, PCV (Hct) with p=0.00002216, WBC with p=0.00212, PEFR with p value 3.689 x 10-07.